plz give me the answer
Attachments:
![](https://hi-static.z-dn.net/files/dd4/2acdd115bcfb74c70a9a2e8a10a3e8fd.jpg)
Answers
Answered by
3
Euclid axiom is if one thing equal to samething then they are equal to one another
given=AC=BD
prove that AB=CD
AC-BC=CD. 1) statement
BD-BC=AB
so we can say that
by
1)statement AC +CD = AC+ AB (because AC=BD so we can write AC in the place of BD)
:--hence proved CD=AB( AC is subtracted from both side)
given=AC=BD
prove that AB=CD
AC-BC=CD. 1) statement
BD-BC=AB
so we can say that
by
1)statement AC +CD = AC+ AB (because AC=BD so we can write AC in the place of BD)
:--hence proved CD=AB( AC is subtracted from both side)
Answered by
0
Answer:
1st photo is wrong second is right
Attachments:
![](https://hi-static.z-dn.net/files/ddc/3f3d2e9709f85cc8c6cb6b0c8c13520a.jpg)
![](https://hi-static.z-dn.net/files/d3b/e433a7f871949baf32275f094cd444ef.jpg)
Similar questions